SURVEY OF MACHINE LEARNING APPLICATIONS IN MEDICAL IMAGING. ALGORITHMS AND TECHNOLOGIES - Marius Eremia Vlaicu POPA; Mihai CRUCERU; Bogdan DIACONU (Fiabilitate şi Durabilitate)
A literature survey was conducted attempting to report usage of Machine Learning (ML) algorithms in processing and interpretation of medical images (X-ray, CT scan, MRI, DEXA, etc.) for the purpose of diagnosing orthopedic disorders. ML algorithms and technologies developed exponentially over the last decades triggered by advances in processing capacity, open-source ML platforms, frameworks and libraries (Anaconda, Scikit, TensorFlow, OpenNN, Torch and so on).